2017
DOI: 10.1108/medar-02-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting

Abstract: Purpose Sustainability reporting serves as a means of communication between corporations and their stakeholders on sustainability issues. This study aims to identify and account for the contents of sustainability reporting communicated through the websites of the plants in five continents of the same multinational mining corporation. Design/methodology/approach This study uses data published by Newmont Mining Corporation. The corporation has regional headquarters in five continents: Africa, Asia, Australia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 90 publications
1
33
0
Order By: Relevance
“…In agreement with other studies, for instance, on the UN Global Compact (Janney et al , 2009), we found differences in SDG reporting across regions. In addition to a high adoption rate in Europe, we found the highest rate in South America, which stems from the higher governmental regulations and institutional isomorphism (Amoako et al , 2017). Nevertheless, if we add firm characteristics and accountability measures, such as external auditing, the regional effect becomes nonsignificant.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 83%
“…In agreement with other studies, for instance, on the UN Global Compact (Janney et al , 2009), we found differences in SDG reporting across regions. In addition to a high adoption rate in Europe, we found the highest rate in South America, which stems from the higher governmental regulations and institutional isomorphism (Amoako et al , 2017). Nevertheless, if we add firm characteristics and accountability measures, such as external auditing, the regional effect becomes nonsignificant.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 83%
“…A few studies reported that the extent of sustainability and SDGs disclosure is gradually increasing in the region (Arthur et al, 2017; Bananuka, Tauringana, & Tumwebaze, 2022; Injeni et al, 2021; Kabir & Akinnusi, 2012; Soobaroyen et al, 2023; Stolowy & Paugam, 2018; Tumwebaze et al, 2022). The vast majority, however, denied this evidence and rather noted that the extent of reporting in the continent is very low and unsatisfactory (Ahmad & Gao, 2005; Akrout & Ben Othman, 2016; Alshbili et al, 2020; Amoako et al, 2017; Baba & Baba, 2021; Bhatia & Makkar, 2020; Bose & Khan, 2022; Crous et al, 2021; Erin & Bamigboye, 2022; Haladu & Bin‐Nashwan, 2022; Iredele, 2020; Lauesen, 2016; Marx & van Dyk, 2011; Mathuva & Kiweu, 2016; Taiwo et al, 2021; Tilt et al, 2021).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Among these groups, the understanding of philanthropy and accountability is different and there is also a mismatch between the operational scope of these NGOs and the real intention for their existence. While most of the local NGOs are owned by politicians or their cronies [101] whose interest on behalf of the general public is questionable, others may not really understand the concept or mechanisms for pursuing sustainability and/or accountability. This implies that the population of the less privileged and the deprived will continue to suffer, and the targeted need will remain unaddressed, thereby reducing the quality of life, and fuelling underdevelopment and poverty all of which negates the NGOs' existence ab initio since they are primarily set up to fight these by improving the quality of life.…”
Section: Sr Driversmentioning
confidence: 99%
“…Other than providing a platform for entrenching accountability and transparency as well as setting an example for others to follow, SR by NGOs can result in several benefits for both the NGOs and the society at large [25,101]. SR has the capacity to highlight hidden organisational values that might not be recognised through traditional reporting [17].…”
Section: In His Study Of Partnership Between Corporations and Ngos Through Sustainabilitymentioning
confidence: 99%